Loop scattering in two-dimensional QCD - Abdalla, E.; Abdalla, MCB (American Physical Soc, 1995)
Using the integrability conditions that we recently obtained in two-dimensional QCD with massless fermions we arrive at a sufficient number of conservation laws to fix the scattering amplitudes involving a local version of the Wilson loop operator.